An abolitionist theory on crime: ending the abusive relationship with Racist-Imperialist-Patriarchy [R.I.P.]*. Issue 4 (2nd October 2017) - Saleh-Hanna, Viviane
Abstract: In this article I re-assess the parameters of what we seek to abolish as we pursue penal abolition. I apply Black Feminist Hauntology to exorcize the barriers of traditional and ineffective deconstructions of crime and criminalization. To illustrate these weaknesses I discuss police killings and related vigilante white supremacist violence. I present the aftermath of the deaths and trials (when there were trials) to bring to light the large disconnects that exist between abolitionism and the world in which crime lives. To begin to address this disconnect I present an abolitionist theory on crime founded upon five pillars of assessment: abolition's perceived minimization of violence; the abusive R.I.P. relationship between crime and justice; a cultural phenomenon of achieving significance through proximity or by association; abusive naturalizations of violence that have been unaddressed in penal abolition; locating the struggles to exit abusive relationships within the core of our studies of criminal justice and penal abolition. I conclude that when penal abolitionists conceive of crime as a social construction tied to criminal justice institutions alone, as opposed to part of a structurally Racist-Imperialist-Patriarchal [R-I-P] abusive relationship, they stunt the possibilities of abolition in manners akin to pushing against a 500 year old tree from its trunk and expecting it to topple over without any account for the roots that hold it firmly in the ground.